Double Burden of Nutrition and some Eating Habits Characteristics of Preschool Children in Nam Hong Commune, Dong Anh district, Hanoi, 2018 - Thi Tuyet, Le; Thi Trung Thu, Nguyen; Thi Thu Hoai, Ngo; Thi Lan Huong, Nguyen; Thi Thuy Dung, Le; Nam Khanh, Do (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2019)
A b stract : The study aims to provide evidence of double nutritional burden (including malnutrition and overweight/obesity) as well as the impact of eating habits on nutritional status of preschool children at Nam Hong commune, Dong Anh district, Hanoi. Subjects of study: children aged from 24 to 60 months old at 2 preschools of Nam Hong commune. The study is divided into 2 phases: at the phase 1: a cross sectional study was applied to 1593 children; at the phase 2: a matched case-control study was applied in order to analyze effects of eating habits to nutritional status of children (1 malnourished child / 5 normal children and 1 obese overweight child / 5 normal children, matched pairs in age, sex, class). Research results: the percentage of children with normal nutritional status is 86.8%, however, Nam Hong still suffer a double burden of nutrition when the rate of malnourished children is still high (accounting for 4.2%) and overweight/obesity children is 9.0%, in which the rate of overweight and obesity children in boys is higher than girls (10.9% compared with 6.7%, respectively). Eating characteristics affect malnutrition status of children including: loss appetite (OR=4.3), slowness in eating (OR=2.23), enjoyment of food score (OR=0.69), desire to drink score (OR=0.82). Eating characteristics affect the overweight/obesity child’s include: appetite characteristics (OR=4.24), loss appetite (OR=0.43), fast eating (OR=2.56), slowness eating (OR=0.43), eating more (OR=6.78), eating less (OR=0.31), prefer fat (OR=2.18), food responsiveness score (OR=1.59), enjoyment of food score (OR=1.8), satiety responsiveness score (OR=0.51), slowness in eating score (OR=0.05), emotional under eating score (OR=0.67), food fussioness score (OR=0.72). Keywords Double burdens, malnutrition, overweight/obesity, Nam Hong commune, Dong Anh. References [1] L.T. Huong, N.T. Linh, N.T.T. Ha, Nutritional status and cognitive development of children under 6 in urban, rural and mountainous area of the north in 2012, Journal of Food and Nutrition Sciences 10 (2014) 67-74 (in Vietnamese). http://viendinhduong.vn/research/detail?id=620&catName=cac-de-tai-va-xuat-ban-pham&lang=vi [2] N.T.T. Thu, L.T. Tuyet, Anthropometric characteristics and nutritional status in 24 - 59 months children in Hanoi city, Thanh Hoa province and Phu Tho province in 2018, HNUE Journal of Science, Natural Sciences 3 (2018) 150-157. (in Vietnamese). https://doi.org/10.18173/2354-1059.2018-0016. http://stdb.hnue.edu.vn/portal/journals.php?articleid=5149. [3] N.T.T. Thu, L.T.T. Dung, L.T Tuyet, Nutritional status: the trends of preschool children aged 10–60 months in the north of Vietnam, Health Risk Analysis 4 (2018). https://doi.org/10.21668/health.risk/2018.4.06.eng [4] N.H. Trang, T.K. Hong, M.J. Dibley, Cohort profile: Ho Chi Minh City Youth Cohortdchanges in diet, physical activity, sedentary behaviour and relationship with overweight/obesity in adolescents, BMJ Open 2 (2012) e000362. https://doi.org/10.1136/bmjopen-2011-000362. http://dx.doi.org/10.1136/bmjopen-2011-000362 [5] WHO, fact sheet, 2019. Infant and young child feeding, http://www.who.int/mediacentre/factsheets/fs342/en/ (accessed 6/2019). [6] WHO, Childhood overweight and obesity, 2019. https://www.who.int/dietphysicalactivity/childhood/en/ (accessed 6/2019). [7] J.M. Braun, H.J. Kalkwarf, G.D. Papandonatos, A. Chen, B.P. Lanphear, Patterns of early life body mass index and childhood overweight and obesity status at eight years of age, BMC Pediatr 18 (2018) 161. https://doi.org/10.1186/s12887-018-1124-9. [8] L.T. Tuyet, B.T. Nhung, T.Q. Binh, Association of neonatal, breastfeeding, eating behavior characteristics with obesity in primary school children in Hanoi urban areas, VNU Journal of Science: Natural Sciences and Technology 30 (2014) 275-281. (in Vietnamese). [9] L. Webber, C. Hill, J. Saxton, C.H. Van Jaarsveld, J. Wardle, Eating behaviour and weight in children, Int  J Obes (Lond). 33 (2009) 21-28. https://doi.org/10.1038/ijo.2008.219. [10] A. Meule, A.P. Lutz, C. Vogele, A. Kubler, Impulsive reactions to food-cues predict subsequent food craving. Eat Behav 14 (2014) 99-105. https://doi.org/10.1016/j.eatbeh.2013.10.023. [11] WHO, Anthro Plus for Personal Computers Manual: Software for Assessing  Growth of the World’s Children and Adolescents. Geneva, Switzerland: World Health Organization. http://www.who.int/growthref/tools/en/ (accessed 3/2019). [12] J. Wardle, C.A. Guthrie, S. Sanderson, L. Rapopor, Development of the Children's Eating Behaviour Questionnaire. J Child Psychol Psychiatry 42 (2001) 963-970. https://doi.org/10.1111/1469-7610.00792. [13] Vietnam National Institute of Nutrition, UNICEF, Alive and Thrive, Nutrition monitoring information 2013, Hanoi, Vietnam (2014). [14] UNICEF. Undernutrition contributes to nearly half of all deaths in children under 5 and is widespread in Asia and Africa 2019. 2019. https://data.unicef.org/topic/nutrition/malnutrition/# (accessed 3/2019). [15] M. de Onis, E. Borghi, M. Arimond, P. Webb, T. Croft, K. Saha, et al., Prevalence thresholds for wasting, overweight and stunting in children under 5 years, Public Health Nutr 22 (2019) 175-179. https://doi.org/10.1017/S1368980018002434. [16] A. Ek, K. Sorjonen, K. Eli, L. Lindberg, J. Nyman, C. Marcus, P. Nowicka, Associations between Parental Concerns about Preschoolers' Weight and Eating and Parental Feeding Practices: Results from Analyses of the Child Eating Behavior Questionnaire, the Child Feeding Questionnaire, and the Lifestyle Behavior Checklist, PLoS One 22 (2016) e0147257. https://doi.org/10.1371/journal.pone.0147257. [17] J. Zhang, Y. Zhai, X.Q. Feng, W.R. Li, Y.B. Lyu, T. Astell-Burt, P.Y. Zhao, X.M. Shi, Gender differences in the prevalence of overweight and obesity, associated behaviors, and weight-related perceptions in a National Survey of Primary School Children in China, Biomed Environ Sci 31 (2018) 1-11. https://doi.org/10.3967/bes2018.001. [18] V.H.C. Wang, J. Min, H. Xue, S. Du, F. Xu, H. Wang, Y. Wang, Factors contributing to sex differences in childhood obesity prevalence in China, Public Health Nutr 21 (2018) 2056-2064. https://doi.org/10.1017/S1368980018000290. [19] H. Ochiai, T. Shirasawa, R. Nishimura, A. Morimoto, N. Shimada, T. Ohtsu, M. Hashimoto, H. Hoshino, N. Tajima, A. Kokaze, Eating behavior and childhood overweight among population-based elementary school children in Japan, Int J Environ Res Public Health 9 (2012) 1398-1410. https://doi.org/10.3390/ijerph9041398. [20] L.T. Tuyet, B.T Nhung, T.Q Binh, Association of some eating behaviour characteristics and sedentary lifestyle with obesity among Hanoi primary school boy in 2012, VNU Journal of Science: Natural Sciences and Technology 31 (2), 60-66 (in Vietnamese). https://js.vnu.edu.vn/NST/article/view/76. [21] W. Labree W., D. van de Mheen, F. Rutten, G. Rodenburg, G. Koopmans, M. Foets, Differences in Overweight and Obesity among Children from Migrant and Native Origin: The Role of Physical Activity, Dietary Intake, and Sleep Duration, PLoS One 10 (2015) e0123672. https://doi.org/10.1371/journal.pone.0123672. [22] S. Kar, B. Khandelwal, Fast foods and physical inactivity are risk factors for obesity and hypertension among adolescent school children in east district of Sikkim, India, J Nat Sci Biol Med 6 (2015) 356-359. https://doi.org/10.4103/0976-9668.160004. [23] J.L. Santos, J.A. Ho-Urriola, A. Gonzalez, S.V. Smalley, P. Dominguez-Vasquez, R. Cataldo, Association between eating behavior scores and obesity in Chilean children, Nutr J. 10 (2011) 108. https://doi.org/10.1186/1475-2891-10-108. [24] J.C. Spence, V. Carson, L. Casey, N. Boule, Examining behavioural susceptibility to obesity among Canadian pre-school children: the role of eating behaviours, Int J Pediatr Obes 6 (2011) e501–7. https://doi.org/10.3109/17477166.2010.512087. [25] Y.T. Cao, V. Svensson, C. Marcus, J. Zhang, J.D. Zhang, T. Sobko, Eating behaviour patterns in Chinese children aged 12-18 months and association with relative weight - factorial validation of the Children's Eating Behaviour Questionnaire, Int J Behav Nutr Phys Act 9 (2012) 5. https://doi.org/10.1186/1479-5868-9-5. [26] A.T.N. Nguyen, M. Nishijo, T.T. Pham, N.N. Tran, A.H. Tran, L.V. Hoang, H. Boda, Y. Morikawa, Y. Nishino, H. Nishijo, Sex-specific effects of perinatal dioxin exposure on eating behavior in 3-year-old Vietnamese children, BMC Pediatr. 18 (2018) 213. https://doi.org/10.1186/s12887-018-1171-2.